Information & Effect: An Introduction to the Concept Of Immanence as a Physical Quantity - Jöge, Friedhelm M. (European Journal of Applied Sciences, 2023)
The introduction and application of the concept of immanence as a physical quantity allows a broader understanding of effect. Mathematical formulations present the complementary co-factors of information and immanence as the cause and result respectively of the thermodynamic effect. Thus, the concept of immanence helps to clear up the relation between the concepts of information and reality and leads to the derivative of the principle of immanence development which might be applied to problems in astrophysics, e.g. in the discussion on the information paradox (i.e. the question of information loss regarding black holes).